Little Brazil : an ethnography of Brazilian immigrants in New York City - Margolis, Maxine L., 1942- (Princeton University Press, 1994)
Walking west on 4th Street in Manhattan, just three blocks from Rockefeller Center, one passes Brazilian restaurants, the office of New York's Brazilian newspaper, a Brazilian travel agency, a business that sends remittances and wires flowers to Brazil, and a store that sells Brazilian food products, magazines, newspapers, videos, and tapes. These businesses are the tip of an ethnic iceberg, an unseen minority estimated to number some 80,000 to 100,000 Brazilians in the New York metropolitan area alone. Despite their numbers, the lives of these people remain largely hidden to scholars and the public alike. Now Maxine L. Margolis remedies this neglect with a fascinating and accessible account of the lives of New York's Brazilians. Showing that these immigrants belie American stereotypes, Margolis reveals that they are largely from the middle strata of Brazilian society: many, in fact, have university educations. Not driven by dire poverty or political repression, they are fleeing from chaotic economic conditions that prevent them from maintaining a middle-class standard of living in Brazil. But despite their class origin and education, with little English and no work papers, many are forced to take menial jobs after their arrival in the United States. Little Brazil is not an insentient statistical portrait of this population writ large, but a nuanced account that captures what it is like to be a new immigrant in this most cosmopolitan of world cities.